Citrus reticulataÃ¢â¬â¢s Peels Modulate Blood Cholesterol Profile and IncreaseBone Density of Ovariectomized Rats - Adelina, Rosa; Supriyati, Maria Dwi; Nawangsari, Dwi Ana; Jenie, Riris I; Meiyanto, Edy (Universitas Gadjah Mada, 2008)
Hormon Replacement Therapy is a common therapy for estrogen deficiency but in other side it will increase the risk of cardiovascular disease. Another alternative therapy which relatively more safe is using phytoestrogen. The Citrus reticulata’s peel contain flavanone and polimethoxyflavone which are suspected to give estrogenic effect, therefore it is potential to be used as phytoestrogen.The purpose of this study was to examine the estrogenic effect of Citrus reticulata’s peel extract in modulation of bone density and blood cholesterol profile of ovariectomized rats (OVX), an animal model of postmenopausal osteoporosis. Thirty six 7-weeks-old female Sprague Dawley rats were assigned to six groups: a SO group, an OVX group, an OVX+CMCNa group, an OVX+extract dose 500 mg/kgBW group, an OVX+extract dose 1000 mg/kgBW group, and an OVX+estradiol group. After 7 weeks, the rats were killed then blood and femoral were collected immediately. The rontgenogram indicated that extract and estradiol administration increase the bone density. And the data analysis with Oneway ANOVA test ,followed by Shceffé test (P 0.05) showed that extract can improve blood cholesterol profile in dose depend manner. These results suggest a possible role of Citrus reticulata’s peel extract as women’s health agent because of its beneficial effects on bone and lipids.